Yume Enterprise: Dirtbuster56 - automatic cleaning window expert / Muhammad Taufiq Mohd Zainuddin [et al.] - Mohd Zainuddin, Muhammad Taufiq; Mohd Zahib, Zairin; Mohamad Yasin, Ezma Nur Shahira; Rusni, Nur Shahira; Md Zubir, Mariam; Nordin, Nur Kharina (2016)
YUME Enterprise is a new company that operated in Malaysia. It is the first company that being managed by Bumiputera. As for the business we are providing a newly invented technology which is Automatic Cleaning Window Expert. As we go thru with technology grow so our surveying that we are going to provide this machine to the entire nations so that this technology can be used by all people in this country